2016
DOI: 10.4081/aiua.2016.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic assessment of recurrent and first renal calcium oxalate stone formers

Abstract: This study revealed a metabolic tendency to hypercalciuria in calcium oxalate stone patients, predominantly in those with recurrent calcium oxalate urolithiasis. Urinary oxalate excretion was found to be higher in recurrent urolithiasis in comparison to the first episode of calcium oxalate urolithiasis and urinary citrate excretion lower in recurrent urolithiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Some of the promoters include cell membrane lipids (phospholipids, cholesterol, and glycolipids) [ 42 ], calcitriol hormone enhancement via parathyroid hormone stimulation [ 101 ], oxalate, calcium, sodium, cystine, and low urine volume [ 34 ]. Among recurrent stone formers, urinary oxalate excretion was found to be higher, whereas citrate excretion was lower [ 102 ]. Studies indicated that oxalate can increase chloride, sodium, and water reabsorption in the proximal tubule and activate multiple signaling pathways in renal epithelial cells [ 103 ].…”
Section: Mechanisms Of Renal Stone Formationmentioning
confidence: 99%
“…Some of the promoters include cell membrane lipids (phospholipids, cholesterol, and glycolipids) [ 42 ], calcitriol hormone enhancement via parathyroid hormone stimulation [ 101 ], oxalate, calcium, sodium, cystine, and low urine volume [ 34 ]. Among recurrent stone formers, urinary oxalate excretion was found to be higher, whereas citrate excretion was lower [ 102 ]. Studies indicated that oxalate can increase chloride, sodium, and water reabsorption in the proximal tubule and activate multiple signaling pathways in renal epithelial cells [ 103 ].…”
Section: Mechanisms Of Renal Stone Formationmentioning
confidence: 99%
“…[15] Recurrent stone-formers were found to excrete more oxalate from their urine than citrate. [52] Oxalate has been shown in studies to trigger a variety of signaling pathways in renal epithelial cells, as often it enhances the reabsorption of water, sodium, and chloride in the proximal tubule. [53] In general, it has been hypothesized that the cause of stone formation is a mismatch between urinary stone inhibitors and promoters.…”
Section: Renal Stones Inhibitors and Promotersmentioning
confidence: 99%
“…According to [16], variety of chemicals were preferred for induction of renal calculi in experimental animal through the exogenous administration of lithogenic material including sodium oxalate, glycolic acid, ethylene glycol (EG) and Hydroxyl-L-proline. The administration of the dose can be done by intra-peritoneal administration or by subcutaneous somatic minipump and also can be induced as miscible dose of toxicants with drinking water under oral administration method [17].…”
Section: Selection Of the Toxicantmentioning
confidence: 99%